Draft Annual Plan 1990-91 Volume : I An Overview Government of Assam - Planning Commission (Planning Commission, 1990)
Assam is situated in the North-Eastern corner of the country and forms the core of the North-Eastern Region comprising Arunachal Pradesh, Manipur, Nagaland, Meghalaya, Mizoram and Tripura. It has common borders with all the six States of the region along with West Bengal besides into national borders with Bangladesh and Bhutan and is linked with the rest of India by a narrow corridor through North Bengal.
Planning and Development Department
Government of Assam Planning and Development Department